Chemical Composition of Calculi Removed from Urinary Tract : Chemical Composition of Urinary Calculi - Raza Asghar, Hassan; Ahmad, Muhammad Zahid; Asif, Muhammad; Channa, Aftab Ahmed; Ahmad, Nauman; Niazi, Abdul Basit; Shahzad, Shafqat (Pakistan Journal of Health Sciences, 2023)
Urinary stone (calculi) disease is the most prevalent occurrence in the outpatient urology department by far. It is becoming more and more commonplace. Since most of the calculi might recur, understanding chemical composition is crucial. worldwide. Objective: To analyze the different compositions of calculi removed from urinary tract. Methods: A descriptive study was performed in the Department of Urology, Avicenna Medical College and Hospital, Lahore, from July 2016 to October 2022. 300 Patients operated for urinary stone disease were selected as the sample population. All calculi removed from these patients were subjected to stone analysis and then results were prepared. Results: The most common stone type based on chemical composition was calcium oxalate (52%), followed by uric acid stones (25%), mixed stones (17%) and magnesium ammonium phosphate MAP (5%). Other less common types were accountable for only 1%. Conclusions: Calcium oxalate, uric acid and mixed composition stones are most common varieties in the draining area of our hospital setup.